Midwinter blood - Sedgwick, Marcus (New York : Roaring Brook Press, 2013)
"Seven linked vignettes unfold on a Scandinavian island inhabited--throughout various time periods--by Vikings, vampires, ghosts, and a curiously powerful plant"--Provided by publisher.
On the remote Scandinavian island of Blessed, a curiously powerful plant that resembles a dragon grows. What secrets lurk beneath the surface of this idyllic countryside? And what might be powerful enough to break the cycle of midwinterblood? We travel from 2073 to the age of the Vikings and back to Time Unknown, as we meet an archaeologist, a painter, a ghost, a vampire, and are carried on a current of cursed love and reincarnation.
Midsummer sun : June 2073, the flower moon -- The archaeologist : July 2011, the hay moon -- The airman : August 1944, the grain moon -- The painter : September 1902, the fruit moon -- The unquiet grave : October 1848, the hunter's moon -- The vampire : 10th century, the snow moon -- Midwinter blood : time unknown, the blood moon.
Originally published in the United Kingdom by Orion Children's Books in 2011.
Novel.
Keywords: Man-woman relationships -- Juvenile fiction; Reincarnation -- Juvenile fiction; Islands -- Juvenile fiction; Scandinavia -- History -- Juvenile fiction; Young adult fiction; Paranormal romance stories; Young adult fiction; Michael L. Printz book award: Winner -- 2014.